2021
DOI: 10.1002/ams2.706
|View full text |Cite
|
Sign up to set email alerts
|

Japanese rapid/living recommendations on drug management for COVID‐19: updated guidelines (September 2021)

Abstract: Background:The coronavirus disease 2019 (COVID-19) has spread worldwide since early 2020, and there are still no signs of resolution. The Japanese Clinical Practice Guidelines for the Management of Sepsis and Septic Shock (J-SSCG) 2020 Special Committee created the Japanese rapid/living recommendations on drug management for COVID-19 using the experience of creating the J-SSCG. Methods:The Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) approach was used to determine the certainty of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…In conclusion, in the USA 126 and Japan 127 (in consideration by the EMA) baricitinib in combination with low-dose dexamethasone is currently recommended for the treatment of COVID-19 patients requiring high-flow oxygen or non-invasive ventilation or low-flow oxygen but with significantly elevated inflammatory markers. The same conclusions were reached by the WHO from the eighth version of its ‘A living WHO guideline on drugs for COVID-19’ from January 2022, which strongly recommended baricitinib for patients with severe or critical COVID-19 in combination with corticosteroids.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, in the USA 126 and Japan 127 (in consideration by the EMA) baricitinib in combination with low-dose dexamethasone is currently recommended for the treatment of COVID-19 patients requiring high-flow oxygen or non-invasive ventilation or low-flow oxygen but with significantly elevated inflammatory markers. The same conclusions were reached by the WHO from the eighth version of its ‘A living WHO guideline on drugs for COVID-19’ from January 2022, which strongly recommended baricitinib for patients with severe or critical COVID-19 in combination with corticosteroids.…”
Section: Introductionmentioning
confidence: 99%
“…Among those published or updated since 2021, the year that RCTs comparing different intensities of anticoagulation were first published, both the Japanese living guidelines on drug management for COVID-19 23 and the European Respiratory Society living guidelines 24 recommend anticoagulation in patients with COVID-19-related critical illness, but do not specify an intensity. By contrast, the French guideline 25 suggests that patients with severe COVID-19 (oxygen requirement greater than 6 L/min or mechanical ventilation) should receive at least intermediate dose prophylactic anticoagulation, although these guidelines were written before the publication of the multiplatform 18 [27][28][29] Major differences between the ASH guidelines and these other documents include use of high-quality systematic reviews and EtD frameworks, marker states to estimate the relative importance of key outcomes to patients, and decision thresholds to facilitate judgments about the magnitude of desirable and undesirable effects.…”
Section: What Are Others Saying and What Is New In These Guidelines?mentioning
confidence: 99%
“…Consequently, these authors concluded that a quite different hematological phenotype is present in COVID-19-induced coagulopathy compared with that seen in typical sepsis-induced DIC, in which local thrombus formation might be promoted in severe COVID-19. Now, even though a clear treatment option using anticoagulants is available to patients with moderate-to-severe COVID-19 [ 5 , 6 , 7 ], a further clarification of the mechanisms of the coagulation abnormality is still warranted.…”
Section: Etiology and Pathophysiology Of Dicmentioning
confidence: 99%